A descriptive investigation of Malaysian internet users’ adoption of online shopping - Norazah Mohd Suki (Penerbit UKM, 2006)
The rapid adoption of the Internet as a commercial tool has resulted in firms trying to do business in innovative ways of marketing in computer-mediated environments. As more businesses connect to the Internet, consumers will have wider choices in gathering products or services with respect to the latest information in a global online marketplace. This study focuses on providing a deeper insight into the Malaysian Internet users’ behaviour and adoption of browsing or purchasing products and services through the Internet. It was found that Internet/Non Internet Shopper and years of usage on the Internet was insignificant at 0.05 significance level. Thus, Malaysian Internet users’ who have just experienced browsing the Internet for just one year prior are also attracted to conduct online shopping. They are attracted to the Internet pull factors such as user friendliness and reliability of the products or services offered through the Internet.